2015
DOI: 10.1063/1.4938539
|View full text |Cite
|
Sign up to set email alerts
|

Skyrmion based microwave detectors and harvesting

Abstract: Abstract. Magnetic skyrmions are topologically protected states that are very promising for the design of the next generation of ultralow-power electronic devices. In this letter, we propose a magnetic tunnel junction based spin-transfer torque diode with a magnetic skyrmion as ground state and a perpendicular polarizer patterned as nanocontact for a local injection of the current. The key result is the possibility to achieve sensitivities (i.e. detection voltage over input microwave power) larger than 2000V/W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 42 publications
(42 reference statements)
4
80
0
1
Order By: Relevance
“…We take J=1 for the energy units and take D 0 /J=0. 27. For the inclined magnetic field, we take H z =0.057 with θ being a variable.…”
Section: (C) and (D)]mentioning
confidence: 99%
“…We take J=1 for the energy units and take D 0 /J=0. 27. For the inclined magnetic field, we take H z =0.057 with θ being a variable.…”
Section: (C) and (D)]mentioning
confidence: 99%
“…Similarly to optics2122, the excitation of spiral spin-waves in magnetism could be attractive for designing new information coding protocols. Recent experimental observations have demonstrated that skyrmions1516232425 can be nucleated via conversion of domain walls in Ta/CoFeB/MgO26, or by applying an out-of-plane field in Ir/Co/Pt27 and Pt/Co/MgO28 multilayers. Although a single skyrmion can be nucleated by a spin-polarized scanning tunneling microscope29, the control of its room temperature nucleation is still an experimental challenge.…”
mentioning
confidence: 99%
“…Skyrmion-based devices have also been designed to make logic gates in which the duplication or merging of skyrmions is used to perform logic operations [117]. We could also cite the exploitation of the interaction of magnons with skyrmions for the design of skyrmion magnonic crystals for tunable rf filtering [118] or the development of rf oscillators based on the specific dynamical modes of skyrmionic spin configurations [119].…”
Section: Hdmi = (S1  S2)d12 (Eq2)mentioning
confidence: 99%